A comparison of cultural meanings in Sundanese and Korean traditional children's songs: An anthropologist study - Lia Amelia Nurkhazanah; Yulianeta Yulianeta; Didin Samsudin (Journal of Korean Applied Linguistics, 2021)
Traditional children's songs are a literary heritage that contains cultural values and noble norms that are meaningful in people's lives. This research aims to describe the (1) comparison of the linguistic units, and (2) comparison of cultural meaning in Sundanese and Korean traditional children’s songs. The data were taken from four Sundanese and Korean children folk songs’ lyrics. This research method is a qualitative descriptive based on an anthropolinguistic approach, and the data were collected by downloading the lyrics on youtube. The data were analyzed using the distributional and identify method. The results show that both in Sundanese and Korean traditional children’s songs lyrics consist of linguistic units words, phrases, clauses, sentences, and discourse. In the realm of anthropolinguistics, the results show similar cultural meanings in (1) Ayun Ambing and Jajang Jajang Uri Aga (자장 자장 우리 아가) which is the cultural meaning of cradling a baby, family love and respect for parents. (2) in Bulantok and Dal-dal Museun Dal (달달 무슨 달) include the meaning of being grateful for the beauty of nature, (3) in Cing Cangkeling and Saeya- saeya Pharangsaeya (새야 새야 파랑새야) shows the meaning of vigilance against colonizer, (4) in Oyong-oyong Bangkong and Dukkeoba-dukkeoba (두껍아-두껍아) contains cooperation and life guidance. This research is expected to be used as a means of preserving language and culture through traditional songs.